The effectiveness of social media in assisting opinion leaders to disseminate political ideologies in developing countries: the case of Malaysia - Nuurrianti Jalli (Penerbit Universiti Kebangsaan Malaysia, 2016)
When the Internet started to be widely used by the people around the world in the 90s, this technology was seen as a promising alternative for the traditional media outlets, especially in the countries where the people in power (i.e: the government) control the media organs. By controlling major media organs, by logic, people in power can easily manipulating the information with agendas of their interests before providing them to the general public. Hence, the general public is fed with information that has been specifically altered, which, in the long run will have effects on the public’s perceptions towards various thing especially their perceptions towards the people in power. In this paper, the researcher explores the effectiveness of the Internet, especially social media in assisting opinion leaders to disseminate political ideologies in Malaysia. Through examining the Malaysian media structure, an interview with eight Malaysian opinion leaders, the researcher finds that although to a certain extent the Internet provides alternative for the people to voice their opinions, the effectiveness of Internet based platforms like social media actually depends on how one utilizes it. Through interviews with the Malaysian opinion leaders, the researcher also investigates how the current Malaysian laws (especially media related laws) affect how the general public voices their opinions online.